Efeito da intoxicação por metilmercúrio no perfil lipídico, alterações no tecido adiposo branco epididimário e fígado de camundongos C5BL6/J APOE nocautes - Braga, Synara Cavalcante Lopes (2022)
Mercury (Hg) is a heavy metal and the third most toxic element on the planet. Mercury intoxication is a public health problem in endemic regions of Brazil, especially in the Amazon region. Recently, evidence pointed to an effect of mercury intoxication on cardiovascular and atherosclerotic risk. On the other hand, the obesity pandemic is a global concern that affects all age groups, increasing the risk of cardiovascular and chronic-degenerative diseases. In this study, we evaluated the effect of methylmercury intoxication (MeHg) (20mg/L in drinking water for 20 days) on structural and functional changes in the epididymal white fat tissue in male ApoE knockout (ApoE ko) and wild-type (25-30 g weight) mice. ApoE ko animals are dyslipidemic, being used as experimental model of cardiovascular disease. Delta and weight gain, epididymal adipose tissue and liver weight, plasma concentrations of leptin, triglycerides, and cholesterol were investigated. To assess liver injury, liver assays of hydroperoxide, superoxide dismutation (SOD), thiobarbituric acid-reactive substances (TBARs), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and hepatic steatosis score were analyzed. In addition, gene expression of LCAT, NFkB, HMGCR, ApoA1, TNF-α, and PPAR and the epididymal adipose tissue morphometry were analyzed. MeHg intoxication reduced weight gain of MeHg-intoxicated wild-type animals when compared to their controls (p<0.05). Epididymal adipose tissue weight and leptin plasma concentrations were lower in ApoE ko control and in intoxicated mice when compared to wild-type controls (p<0.05). Plasma concentrations of triglycerides and total cholesterol were higher in ApoE ko mice with or without MeHg intoxication (p<0.05). Total cholesterol concentrations were significantly higher in ApoE ko intoxicated when compared to ApoE ko controls. Liver weight was higher (p<0.05) in the intoxicated ApoE ko group when compared to the wild-type control group. Hepatic steatosis was detected in intoxicated ApoE ko mice when compared to wild-type controls and was increased in intoxicated ApoE ko mice when compared to ApoE ko controls (p<0.05). Intoxicated animals showed higher concentrations of TBARS regardless of the presence or absence of ApoE (p<0.05). SOD concentrations were significantly higher in intoxicated wild-type and Apoe ko animals when compared to their respective controls (p<0.05). ALT and AST concentrations were higher in ApoE ko animals regardless of MeHg intoxication. No differences were found in gene expressions of LCAT, NFB, HMGCR, ApoA1, TNFα, and PPAR between the groups studied. The mean diameter of adipocytes was smaller in ApoE ko controls and intoxicated, when compared to wild-type animals (p<0.05). The results suggest that ApoE deficiency and MeHg intoxication affect the structure and function of adipose tissue and cause hepatic changes.